2007
DOI: 10.1017/s1138741600006545
|View full text |Cite
|
Sign up to set email alerts
|

Presaccadic Brain Potentials in Conditions of Covert Attention Orienting

Abstract: Twelve healthy subjects underwent investigation of averaged (electroencephalogram) EEG potentials during preparation for motor activity and in the latent period (LP) of visually evoked saccades by presentation of stimuli using Posner's (1980) design of "cost-benefit." It has been shown that covert spatial attention orientation leads to an increase in amplitude and decrease in latency of presaccadic initiation potential peaks within the saccadic latent period (LP) (P-100, N -50). Processes of covert orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…There are at least three interpretations why playing preferred musical pieces had a beneficial effect on eye tracking. First, music may act as a cue to shift visual attention from one locus to another [32][34]. Visual cueing improves the reaction time of PD subjects on a task in which subjects save a cartoon character from getting run over [35].…”
Section: Discussionmentioning
confidence: 99%
“…There are at least three interpretations why playing preferred musical pieces had a beneficial effect on eye tracking. First, music may act as a cue to shift visual attention from one locus to another [32][34]. Visual cueing improves the reaction time of PD subjects on a task in which subjects save a cartoon character from getting run over [35].…”
Section: Discussionmentioning
confidence: 99%
“…The right FEF might be more involved in AS than PS (Connolly et al 2002;DeSouza et al 2003). Spatiotemporal analyses of presaccadic potentials showed that the right frontal cortex is activated to a greater extent prior to AS than PS (Slavutskaya and Shulgovskii 2007. Apparently, the right hemisphere dominates the preparation and spatial attention and inhibition of automatic saccades to visual stimulation. In a prosaccade, task attention could remain at the location of stimulus as the saccade is directed to the stimulus.…”
Section: Neural Activity In Pro-and Antisaccades: Similarities and DImentioning
confidence: 92%
“…Early this potential was associated with processes of motor preparation, decision-making and movement initiation [5,6,8].…”
Section: Bmentioning
confidence: 99%